Class Readers (Resource Books for Teachers) - Greenwood J.; Maley A. (Oxford Oxford University Press, 2000)
A guide to using readers in the language classroom. The book is divided into three sections: pre-reading, while reading and after reading and includes activities to develop intensive and extensive reading skills, listening activities, writing in various styles and oral tasks. This series gives the classroom teacher a guide to the practice of key aspects in language teaching and considers some of the underlying concepts. In each book an introduction presenting important issues in a key area is followed by examples and discussion of actual classroom materials and techniques.
Keywords: 811.111